Fetal dose estimation in a case of unintended pregnancy during brain radiotherapy. (September 2016) - Figueira, R.; Reis, T.; Carvalho, A.; Souto, C.; Sousa, M.; Monteiro, A.; Inácio, D.; Osório, L.
Abstract : Introduction: Pregnancy during radiotherapy is not a common clinical situation. We describe a fetal dose estimation necessary before starting a course of radiotherapy for a brain tumor in a patient unexpectedly pregnant at the time scheduled for the beginning of treatment. Purpose: To estimated the dose to the fetus during the programmed course of radiotherapy before deciding if the patient should advance with the treatment or not. Materials and methods: The initial plan was optimized to avoid fetus exposure to radiation without compromising dose to the target volume. We considered the real patient distances between plan isocenter and 3 critical points: uterus fundus, umbilical and pubis. Using an anthropomorphic phantom and solid water slabs we positioned an ionizing chamber at different depths, corresponding to these points, and determined the estimated doses for the complete course of radiotherapy. Results: The maximum dose value measured was 2, 5 cGy, well below the 10 cGy reported tolerance value. After explaining the situation to the patient and the risks involved, a decision was taken to go on with the treatment as planned. A set of 3 pairs of TLD dosimeters was used over the patient belly, in these same positions during every treatment fraction. The TLDs readings at the end confirmed the estimated values measured in the phantom. Conclusion: The previous evaluation of the estimated dose to the fetus allowed the patient to successfully complete the radiotherapy course. The pregnancy went on normally and the patient delivered a healthy child. Disclosure: The authors have nothing to disclose.